The Impact of Watching Mukbang on Developing Risk of Eating Disorder Symptoms in Young Adults - Ahmed, Vardah; Aftab, Farah; Ain, Noor ul (Annals of Human and Social Sciences, 2025)
The aim of the current research was to explore the relationship between watching Mukbang and developing the risk of eating disorder symptoms, and how personality traits play a moderating role in young adults The possible consequences of vicarious eating on dietary behavior and the role of personality factors between the variables have not been explored, which is why the current study focused on analyzing these relationships. A quantitative correlational survey was conducted on 101 participants aged 18 to 40. The scales used were the Mukbang Addiction Scale, Eating Attitude Test , and Big Five Personality Inventory. Results indicated a positive correlation between watching Mukbang and eating disorder symptoms; however, personality traits did not play a moderating role. This study helps clinical psychologists conceptualize cases and plan treatment with a new perspective. In future, sample from multiple cities of Paksitan could be inculcate to increase the generalizability of the result.